A Survey on Wireless Sensor Network (WSN): Security Issues, Challenges and Solutions: Exploring Security Issues and Solutions in Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The sensor network security architecture needs to integrate a number of security measures and technologies to protect the network and meet the above ideal requirements. This study describes the complete set of these components (and related technologies) currently under investigation in sensor networks. Wireless Sensor Network technology is combined with processing power wireless communication which makes it lucrative for being exploited in abundance in future. The inclusion of wireless communication technology incurs various types of security threats. Security issues of sensor network are different from that of conventional network. The intent of this paper is to explore the security related issues, challenges and propose some solutions to secure the wireless sensor network (WSN) against security threats. Further, as security being vital to the acceptance and use of sensor network for many applications I have made an in depth threat analysis propose some security mechanism in wireless sensor network.